Teaching Quality Improvement in Graduate Medical Education: An Experiential and Team-Based Approach to the Acquisition of Quality Improvement Competencies. (October 2015) - Hall Barber, Karen; Schultz, Karen; Scott, Abigail; Pollock, Emily; Kotecha, Jyoti; Martin, Danyal
Abstract : Problem: An emerging priority in medical education is the need to facilitate learners' acquisition of quality improvement (QI) competencies. Accreditation bodies in both Canada and the United States have included QI and patient safety in their core competencies. Approach: In 2010, the Department of Family Medicine at Queen's University designed a graduate medical education curriculum to engage residents in a clinical QI program that would meet accreditation requirements. Monthly didactic sessions were combined with an experiential, team-based QI project that aligned with existing clinic priorities. The curriculum spans the first year of residency and is divided into three stages: (1) Engaging, (2) Understanding, and (3) Improving and translating. In Stage 1, teams of residents select a clinical QI topic, engage stakeholders, and collect baseline data related to their topic. In Stage 2, they focus on understanding their problem, interpreting their results, and applying QI tools. In Stage 3, they develop change ideas, translate their knowledge, and prepare to hand over their project. Outcomes: This QI curriculum aided residents in effectively acquiring QI competencies and allowed them to experience real-world challenges, such as securing project buy-in, negotiating with peers, and developing solutions to problems. Unlike in many QI programs, residents learned how to improve quality rather than about QI; thus, they formed the necessary foundation to carry out QI work in the future. Next Steps: The curriculum will be evaluated using a knowledge assessment and satisfaction tool and postproject resident interviews. Facilitators will focus more on improving faculty develop ment in QI. Abstract : Supplemental Digital Content is available in the text.